Beyond Scatter-Hoarding and Frugivory: European Corvids as Overlooked Vectors for a Broad Range of Plants - Green, Andy J.; Elmberg, Johan; Lovas-Kiss, Ádám (Frontiers in Ecology and Evolution, 2019)
It is well known that some members of the crow family (Corvidae) are important for seed dispersal either via frugivory (e.g. when feeding on berries) or by scatter hoarding (e.g. of nuts). Dispersal via gut passage of seeds within a fleshy fruit can be considered “classical endozoochory”. However, corvids are rarely recognized as vectors of plants lacking a fleshy fruit, or a large nut (such as plants with a dry achene, capsule or caryopsis). Dispersal of such seeds via gut passage can be considered “non-classical endozoochory”. A century ago, Heintze (1917a,b, 1918) reported on extensive field studies of seed dispersal by 11 species of European Corvidae. His work is overlooked in contemporary reviews of corvid biology. We resurrect his work, which suggests that contemporary views about seed dispersal by corvids are too narrow. Heintze identified 157 plant taxa from 42 families which were dispersed by corvids by endozoochory, as well as another nine taxa only dispersed by synzoochory (which includes scatter-hoarding). Most (54%) of the plant species dispersed by endozoochory lack a fleshy fruit and have previously been assigned to other dispersal syndromes, mainly associated with wind (10%), self-dispersal (22%) or epizoochory (18%). Plants lacking a fleshy fruit were particularly well represented from the Caryophyllaceae (12 species), Poaceae (14 species) and Polygonaceae (8 species). Of 27 taxa germinated by Heintze from seeds extracted from corvid pellets or faeces (71% of those tested), 20 lack a fleshy fruit. Similarly, of 32 taxa he recorded as seedlings having germinated from pellets in the field, 11 lacked a fleshy fruit. However, Heintze’s quantitative data show that classical endozoochory is dominant in Magpies Pica pica and Hooded Crows Corvus cornix, for which 97% of seeds dispersed were fleshy-fruited. Corvids overlap with waterfowl as vectors of terrestrial plants dispersed by non-classical endozoochory, and 56 species are dispersed by both corvids and dabbling ducks according to the lists of Heintze and Soons et al. (2016). Finally, Heintze´s data show that corvids were already dispersing alien plants in Europe a century ago, such as the North American Dwarf Serviceberry Amelanchier spicata.